Inflammation and vascular permeability correlate with growth in sporadic vestibular schwannoma. Issue 3 (2nd November 2018) - Lewis, Daniel; Roncaroli, Federico; Agushi, Erjon; Mosses, Dominic; Williams, Ricky; Li, Ka-loh; Zhu, Xiaoping; Hinz, Rainer; Atkinson, Ross; Wadeson, Andrea; Hulme, Sharon; Mayers, Helen; et al.
Abstract: Background: Inflammation is hypothesized to be a key event in the growth of sporadic vestibular schwannoma (VS). In this study we sought to investigate the relationship between inflammation and tumor growth in vivo using the PET tracer 11 C-( R )-PK11195 and dynamic contrast enhanced (DCE) MRI derived vascular biomarkers. Methods: Nineteen patients with sporadic VS (8 static, 7 growing, and 4 shrinking tumors) underwent prospective imaging with dynamic 11 C-( R )-PK11195 PET and a comprehensive MR protocol, including high temporal resolution DCE-MRI in 15 patients. An intertumor comparison of 11 C-( R )-PK11195 binding potential (BPND ) and DCE-MRI derived vascular biomarkers ( K trans, v p, v e ) across the 3 different tumor growth cohorts was undertaken. Tissue of 8 tumors was examined with immunohistochemistry markers for inflammation (Iba1), neoplastic cells (S-100 protein), vessels (CD31), the PK11195 target translocator protein (TSPO), fibrinogen for vascular permeability, and proliferation (Ki-67). Results were correlated with PET and DCE-MRI data. Results: Compared with static tumors, growing VS displayed significantly higher mean 11 C-( R )-PK11195 BPND (−0.07 vs 0.47, P = 0.020), and higher mean tumor K trans (0.06 vs 0.14, P = 0.004). Immunohistochemistry confirmed the imaging findings and demonstrated that TSPO is predominantly expressed in macrophages. Within growing VS, macrophages rather than tumor cells accounted for the majority of proliferating cells. Conclusion: We present the first in vivo imaging evidence of increased inflammation within growing sporadic VS. Our results demonstrate that 11 C-( R )-PK11195 specific binding and DCE-MRI derived parameters can be used as imaging biomarkers of inflammation and vascular permeability in this tumor group.